Sustainability of the early Mediterranean agriculture - Ferrio J.P.; Voltas J.; Buxó R.; Rovira N.; Aguilera M.; Bort J.; Serret M.D.; Araus J.L. (Water culture and water conflict in the Mediterranean area, 2008)
Agriculture is still today the main consumer of water in the Mediterranean. We present two cases studies from the edges of Mediterranean Basin which suggest that already early agriculture in the region was not sustainable but exposed to a progressive degradation. One is Tell Halula a site 10 thousand years old from East Mediterranean region of the Fertile Crescent (present-day NE Syria), where Western Agriculture originates. The other site is Los castillejos, a site from South Spain already active about 6 thousand years before present, occupied soon after the arrival of agriculture to the Western extreme of the Mediterranean. For both cases we present a novel approach to study the sustainability of ancient Mediterranean agriculture that combines the measurement of carbon isotope discrimination and nitrogen isotope composition along with the assessment of quality traits in fossil cereal grains.
1. MELIA Workshop Water Culture and Water Conflict, 2007/11/22-25, Nabeul-Médenine (Tunisia)